The Effectiveness Of Mobile Samsat Services in Serving Motor Vehicle Tax Payments in Lumajang Regency - Wena Kusharyanti; Ika Devy Pramudiana; Eny Haryati (Parlementer : Jurnal Studi Hukum dan Administrasi Publik, 2025)
This study aims to describe and analyze: The Effectiveness of Mobile Samsat Services in Serving Motor Vehicle Tax Payments in Lumajang Regency and the factors that affect the Effectiveness of Mobile Samsat Services in Serving Motor Vehicle Tax Payments in Lumajang Regency. The research is a qualitative descriptive analysis. The data analysis technique uses a technique developed by McNabb (2002), namely Grouping the data according to key constructs, identifying bases for interpretation, developing generalizations from the data, Testing Alternative interpretations and Forming and/or refining generalizable theory from case study. The results of the study show that the Mobile Samsat Service has been effective in increasing motor vehicle tax revenue. This program is designed to make it easier for people to pay vehicle taxes, thereby increasing accessibility and convenience. Despite challenges such as technical constraints and time constraints, feedback from the community has been generally positive, stating significant benefits of Samsat Roving in saving time and travel costs. Overall, the Mobile Samsat service in Lumajang Regency has succeeded in creating a mutually beneficial relationship between service providers and customers, which is expected to result in a more positive and trusting relationship between the parties involved. Ease and Accessibility of Services: Taxpayers feel more helped by the services that come directly to them, especially in areas far from UPT offices. The effectiveness of the Mobile Samsat in Lumajang Regency in increasing vehicle tax revenue is influenced by the ease of tax payment, strategic location and operational time, technology adoption, and consistent SOPs. Although it has had a positive impact, continuous efforts are needed to achieve greater inclusivity. These factors are important in improving the effectiveness of vehicle tax services and revenues.